Inhibition of Fibroblast Activation Protein Restores a Balanced Extracellular Matrix and Reduces Fibrosis in Crohn's Disease Strictures Ex Vivo. Issue 2 (18th January 2018) - Truffi, Marta; Sorrentino, Luca; Monieri, Matteo; Fociani, Paolo; Mazzucchelli, Serena; Bonzini, Matteo; Zerbi, Pietro; Sampietro, Gianluca M; Di Sabatino, Antonio; Corsi, Fabio
Abstract: Background: Crohn's disease (CD) is a chronic bowel inflammation that ultimately leads to fibrosis, for which medical therapy is currently unavailable. Fibrotic strictures in CD are characterized by excessive extracellular matrix (ECM) deposition, altered balance between matrix metalloproteinases (MMPs) and their tissue inhibitors (TIMPs), and overexpression of fibroblast activation protein (FAP), a marker of active fibroblasts. Here we investigated the role of FAP-targeted therapy in ECM remodeling in CD strictures ex vivo. Methods: Bowel specimens were obtained from stenotic and nonstenotic ileal segments from 30 patients with fibrostenotic CD undergoing surgery. FAP expression was evaluated in isolated mucosal myofibroblasts by immunoblotting and flow cytometry. Bowel tissue cultures were treated with anti-FAP antibody, and soluble collagen, TIMP-1, and MMPs were measured in tissue culture supernatants by immunoblotting. Anti-FAP-treated myofibroblasts were analyzed for TIMP-1 expression by immunoblotting, for migratory potential by wound healing assay, and for apoptosis by Annexin V staining. Results: Myofibroblasts from stenotic CD mucosa showed upregulation of FAP expression when compared with nonstenotic mucosa. Treatment of stenotic tissues with anti-FAP antibody induced a dose-dependent decrease in collagen production, particularly affecting type I collagen. The treatment also reduced TIMP-1 production in CD strictures, without altering MMP-3 and MMP-12 secretion. Accordingly, anti-FAP treatment inhibited TIMP-1 expression in stenotic CD myofibroblasts and enhanced myofibroblast migration without affecting survival. Conclusions: FAP inhibition reduced type I collagen and TIMP-1 production by CD strictures ex vivo without compromising uninvolved bowel areas. These results suggest that targeting FAP could reconstitute ECM homeostasis in fibrostenotic CD.